Analisis sentimen opini masyarakat terhadap penggunaan layanan maxim menggunakan algoritma naïve bayes - Intania Widyaningrum; Mia Kamayani (Universitas Muhammadiyah Riau, 2023)
Technology is developing very quickly, as is happening in the field of transportation. Currently, transportation has begun to develop with the presence of various online-based transportation. One type of transportation that is widely used is the online motorcycle taxi application called Maxim. This online transportation service is one of the topics that is starting to be widely discussed via Twitter social media. By knowing these sentiments, users can determine whether the online transportation service provider is well received or not. The method used in this research is using the Naïve Bayes algorithm. The aim of this research is to conduct sentiment analysis of public responses regarding online transportation services, namely Maxim. Based on the research results, in evaluation testing, the accuracy results are obtained, namely for negative sentiment getting 87% precision, 74% recall, and 80% f1-score. Meanwhile, positive sentiments get 80% precision, 90% recall, and 85% f1-score. The sentiment results are dominated by positive sentiment, which is as many as 616 data.